An Empirical "Dependent Economy" Model for Pakistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1991)
While the 'dependent economy' approach has been used extensively in theoretical work on developing countries, there is very little empirical analysis of it available in the literature. This paper specifies a dependent economy model which incorporates several developing-country features, including an explicit role for public investment and legal interest rate ceilings. The model is estimated for Pakistan and is used to analyze the country's recent high growth-low inflation experience. In particular, the contribution that external inflows, in the form of workers' remittances and concessional lending, may have made in generating this outcome is assessed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet